The Relationship Between Psychological Empowerment And Career Commitment Of Catholic Religious Education Teachers Post The Covid-19 Pandemic - Winei, Agnes Angi Dian; Jumrio, Edy; Amianu, Echi; Anggraini, Yupi (UNIVERSITAS PAKUAN, 2023)
This research describes the relationship between psychological differentiation and career commitment of Catholic Religious Education teachers after the Covid-19 pandemic. The research uses a quantitative approach and the sampling technique used is Purposive samplingwith the criteria of Catholic Religious Teachers who are in the Palangka Raya Diocese and have worked for a maximum of 5 years so that as many as 30 teachers were obtained as resource persons.. The research instruments used were the Psychological Empowerment scale with a reliability coefficient of 0.899 with 22 valid items, and the Career Commitment scale had a reliability coefficient of 0.935 with 22 valid items which were distributed via Google Form media. Data were analyzed using the Pearson Product Moment correlation analysis technique through the IBM SPSS 25 program. The results of data analysis were a value of r = 0.592 with p = 0.001 (p0.01), so it can be concluded that there is a significant relationship between psychological empowerment and teacher career commitment Catholicism after the Covid 19 pandemic.